Pentingnya Sarana Marketplace Untuk Mendongkrak Usaha UMKM - Bunyamin Bunyamin; Siti Munfaqiroh; Tutik Arniati; Istutik Istutik; Sherly H Erawati; Enggar Nursasi; Moh Soedarman; Muniroh Muniroh (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2022)
Marketplace as one of the products of technological development which is an online media that can be used as a place for marketing products electronically that brings together many sellers and buyers to transact with each other. Partners in this Community Service Program are MSMEs and independent entrepreneurs in the Blimbing sub-district, Blimbing sub-district, Malang City. The method of implementing this service is the interview, presentation and discussion method. Based on the results of the interview, it can be concluded that the problems that occur are: (1). Lack of knowledge of SME business actors and independent businesses about what and how digital marketing/marketplace and or e-commerce are. (2). The lack of knowledge and understanding of how to enter and utilize the digital marketplace market and no training has ever been held on the use of the digital market to improve and develop an effective and efficient business. The solutions offered in this service are as follows: (1). Provide education/knowledge about the importance of how to market MSME products on the Marketplace. The service team provides education/knowledge about how to sell successfully on the Marketplace, by providing exposure ranging from: Paying attention to product appearance, Selection of product names must be correct, clear descriptions, insurance and returns, setting prices, multiplying products sold, Utilizing brands and seasons, Commitment, Gives a personal touch. (2.) Provide education and understanding, terms and signs prohibiting entering the Marketplace, starting from: What documents are needed; Types of products that are prohibited from being sold on the Marketplace (3). Provide education and understanding on how to enter and access media in the Marketplace.